Understanding financial stability - Ramlall, Indranarain (Theory and practice of financial stability, 2019)
Since the outbreak of the US subprime crisis in 2007, financial stability has become a pressing item in the agenda of governments and policy-makers worldwide. However, to date, there are no books that provide a comprehensive analysis of financial stability in all of its dimensions. Understanding Financial Stability undertakes an in-depth analysis of all the concepts and issues related to financial stability. It establishes a general framework for a holistic assessment of financial stability, provides a comprehensive analysis pertaining to the genesis of financial crises, and offers key terms and elements embodied in financial stability. Posing the question of whether financial stability should rely only on resilience or predictability issues when it comes to handling crises, the book provides: Extensive coverage of all key issues involved in the field of financial stability. A consideration of the political economy. A complete and in-depth assessment of crises in the world based on full historical coverage; including a definition of crises, various theories of crises, costs related to crises, types of crises and policy responses to crises. This book will prove valuable to central bankers, economists, and policy-makers who are involved in the field of financial stability, as well as researchers studying the field.